Parameter Pengawasan Politik Dewan Perwakilan Rakyat Republik Indonesia Menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Hananto Widodo (Faculty of Law Hang Tuah University, 2019)
Amendments to the 1945 Constitution have provided support to the DPR, including strengthening the DPR's oversight function. Article 22 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The DPR's supervisory function as a compilatory composer is elaborated in Article 79 paragraphs (2) and (3) of Law No. 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council and the Regional People's Representative Council (MD3). In Article 79 paragraphs (2) and (3) of MD3 Law only norms are formulated which become the object of interpellation and the questionnaire rights are legislation and policies. The formulation of Article 79 paragraphs (2) and (3) does not explain the parameters used by the DPR to request policies from the Government. The purpose of this article is to provide parameters for the use of interpellation rights and questionnaire rights to government policies. This type of research in this paper is normative research. With primary legal material for the 1945 Constitution of the Republic of Indonesia and Law No. 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council and the Regional People's Representative Council (MD3). The parameters of the right of interpellation and the right of questionnaire to government policies that were born from free government authority are general principles of good governance (AAUPB).